Analytical Study on Approximate ð-Birkhoff-James Orthogonality - Jhonny, Saied A.; Ahmed, Buthainah A. (Iraqi Journal of Science, 2020)
In this paper, we obtain a complete characterization for the norm and the minimum norm attainment sets of bounded linear operators on a real Banach spaces at a vector in the unit sphere, using approximate ðœ–-Birkhoff-James orthogonality techniques. As an application of the results, we obtained a useful characterization ofbounded linear operators on a real Banach spaces. Also, using approximate ðœ–-Birkhoff -James orthogonality proved that a Banach space is a reflexive if and only if for any closed hyperspace of , there exists a rank one linear operator such that , for some vectors in and such that ðœ– .Mathematics subject classification (2010): 46B20, 46B04, 47L05.